PERMASALAHAN SISWA DITINJAU DARI BIMBINGAN KONSELING DAN PEMBELAJARAN MATEMATIKA - Putri, Fina Rahma; Hanifah, Hanifah (UNIB Press, 2018)
AbsctractThe purpose of this research was to identify student problems in terms of Counseling Guidance and mathematics learning which is the most frequently problematic fields of study. The method of this research was a qualitative method by generating descriptive data. This data was recorded through field notes. The record of this data was through observation and interviews with teachers of Guidance and Counseling and mathematic at SMAN 3 Bengkulu Tengah with research subjects and informants. The results of this study was the completion steps that are usually carried out by counseling teachers and mathematics teachers in dealing with students who are problematic. Counseling guidance is one of the way to deal with students who are in trouble at school, because students in middle age of school were the transition age of adolescents to adulthood, that is why so many attitudes and mindset are still often changing. One of the most problems that arises was the lack of test scores or the lack of interest of students in mathematics. The conclusion is mathematics teachers can be expected to minimize the causes of these problems.Keywords: Students problems, Counseling Guidance, Mathematics Learning